Case report: Urachal perivascular epithelioid cell tumor - Liu, Mengru; Liang, Pan; Lyu, Dongbo; Zhu, Bingbing; Gao, Jianbo (Frontiers in Oncology, 2024)
Background Urachal tumors are rare in clinical practice, among which urachal adenocarcinoma is the most common. In this study, we report a rare case of urachal perivascular epithelioid cell tumor to improve our understanding of the disease. Case presentation A 26-year-old male patient was hospitalized for lower abdominal pain. The US showed a hypoechoic mass measuring 26mm × 18mm in the superior aspect of the bladder. MRI showed an irregular mass located anterior to the bladder roof, near the midline. The tumor exhibited hypointense on T1WI and heterogeneous hyperintense on T2WI. Additionally, contrast-enhanced T1-weighted imaging revealed obvious ring enhancement of the tumor. The patient underwent surgical resection of the urachal tumor, with subsequent pathological examination revealing a diagnosis of urachal PEComa. Following surgery, the patient underwent regular follow-up assessments, with no evidence of recurrence or metastasis observed after three and a half years. Conclusions Urachal PEComa is a rare mesenchymal tumor that presents challenges in diagnosis through imaging and clinical symptoms. Definitive diagnosis relies on pathological and immunohistochemical analysis. Due to the rarity of urachal PEComa, prognosis assessment necessitates long-term follow-up and evaluation of more cases.